2022
DOI: 10.1177/17407745221103567
|View full text |Cite
|
Sign up to set email alerts
|

When is it impractical to ask informed consent? A systematic review

Abstract: Background Informed consent is one of the cornerstones of biomedical research with human subjects. Research ethics committees may allow for a modification or a waiver of consent when the research has social value, involves minimal risk, and if consent is impractical to obtain. While the conditions of social value and minimal risk have received ample attention in research ethics literature, the impractical condition remains unclear. There seem to be different interpretations of the meaning of impractical within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…In a systematic review of 42 studies, Laurijssen et al found that "impractical" was most commonly used to describe four scenarios that made the informed consent process too demanding for the researchers. These included situations where a full informed process was not possible because (1) patients were too unwell or the guardians too stressed to understand the study; (2) it led to biased selection of patients that invalidates study outcomes; (3) it led to possible harm to the participant (e.g., delaying a potentially life-saving treatment); and (4) it was meaningless for the participant because it did not add to their knowledge about the procedure [25].…”
Section: Studies Where It Is Impractical To Obtain Informed Consentmentioning
confidence: 99%
“…In a systematic review of 42 studies, Laurijssen et al found that "impractical" was most commonly used to describe four scenarios that made the informed consent process too demanding for the researchers. These included situations where a full informed process was not possible because (1) patients were too unwell or the guardians too stressed to understand the study; (2) it led to biased selection of patients that invalidates study outcomes; (3) it led to possible harm to the participant (e.g., delaying a potentially life-saving treatment); and (4) it was meaningless for the participant because it did not add to their knowledge about the procedure [25].…”
Section: Studies Where It Is Impractical To Obtain Informed Consentmentioning
confidence: 99%
“…41,42 Such integration with artificial intelligence with natural language processing algorithms could somewhat alleviate the ongoing ethical dilemma in biomedical EHR-based research regarding the extraction of data from patients' medical records without informed consent. 43,44 In summary, we conclude that standardised psychometric assessments are essential for patients with FEP. Therefore, our proposal of a proxy instrument based on clinical records for the assessment of psychotic and affective symptoms offers a feasible, valid and reliable alternative to standard psychometric procedures in realworld practice settings.…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 79%
“… 41 , 42 Such integration with artificial intelligence with natural language processing algorithms could somewhat alleviate the ongoing ethical dilemma in biomedical EHR-based research regarding the extraction of data from patients’ medical records without informed consent. 43 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…They emphasized the cost to society when excessive focus on consent prevents beneficial CRTs that may be necessary to measure, compare, and improve quality of care. Echoing other studies that revealed challenges of reaching meaningful outcomes when a study is unable to include enough participants due to informed consent requirement or when consent procedures introduce selection bias, 35 most interviewees—with the exception of one REB member with a legal background—used a broader interpretation of burdens and costs in determining whether consent requirements are impractical for a particular CRT. This may be especially relevant to health services trials conducted with smaller clusters by necessity (e.g., due to lower population density), whereby not collecting or including the data from all patients may skew the representativeness of the sample and subsequent study results.…”
Section: Discussionmentioning
confidence: 99%